Analisis Manajemen Risiko pada UMKM “Huma Laundry” Garut - Elky Rimba Priatna; Ghulam Priyatna Yoniar; Dhafin Al-Rasyid Sastradireja; Reihan Ahmad Nurhakim; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to identify and analyze the risks faced by the micro-enterprise Huma Laundry in Tarogong Kaler, Garut, as well as to determine appropriate mitigation strategies to maintain operational stability. The research employed a descriptive qualitative method, with data collected through direct interviews with the owner and observations of the service process. The analysis was conducted by mapping risks based on their likelihood and impact, supported by a SWOT analysis to understand the strategic position of the business. The findings indicate that the main risks encountered by Huma Laundry include machine breakdowns, washing errors, fluctuating income, and delayed payments from regular customers. The SWOT analysis reveals that the business holds strengths such as consistent service quality and a stable customer base, while weaknesses arise from limited digital promotion and simple financial management. Opportunities come from the increasing demand for laundry services, whereas threats include competition and rising operational costs. Recommended mitigation strategies comprise routine machine maintenance, employee training, service quality improvement, digital marketing optimization, and the adoption of non-cash payment systems. Overall, this study highlights the importance of systematic risk management to support the sustainability and competitiveness of micro-enterprises.